PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL STATEMENT PADA PERUSAHAAN SUB SEKTOR KONSTRUKSI DAN BANGUNAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Lubis, Anggi Fadila; Purba, Rahima (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This study aims to determine the effect of pentagon fraud on fraudulent financial statements. The samples that have been collected are 6 companies in the sub-construction infrastructure sector listed on the Indonesia Stock Exchange. The research method uses a purposive sampling method with the number of samples that have been tabulated using associations. Analysis techniques using quantitative methods with descriptive statistical analysis, classical assumption tests (multicollinaryness, heterokedacity and auto correlation), logistic regression analysis and hypothesis testing using the help of SPSS software. The results showed that financial statbility, ineffective monitoring, change in director did not have a positive effect insignificantly, change in auditor, frequent number of ceo's picture had a positive effect not significant. Financial stability is likely because not only management increases profits but funds enter third parties, so that company managers do not feel any pressure obtained from the company's directors to improve finances due to financial stability within the company. Ineffective monitoring of the existence of the board of commissioners in the company so that independent supervision and transparency occur can minimize the occurrence of fraudulent financial statements in the company. Change in director policy is carried out by the stakeholders of the entity to improve the performance of the board of directors owned not for anything else to cover up the fraudulent financial statement. Change in auditor The company changes auditors to cover up the detection of financial statement fraud by old auditors, but the company complies with the regulations set by the Government of the Minister of Finance of Indonesia Number 20 of 2015 article 11 paragraph (1) related to mandatory changes of auditors. Frequent number of ceo's picture appreciation for CEO's who have performed well so that it affects the entity.